Is sleep the red flag to psychopathology's bull?. (29th September 2020) - Gradisar, Michael; Gregory, Alice M.; Tikotzky, Liat
Abstract : 'Hippocrates flagged the value of sleep for good health' was the first line of the Annual Research Review (ARR) by Gregory and Sadeh (2016) in this journal, titled Sleep problems in childhood psychiatric disorders – a review of the latest science . Where Hippocrates has been referred to as the 'Father of Medicine', Professor Avi Sadeh has been respected as a 'Father of Paediatric Sleep Medicine' by those who had the privilege to meet him or read his science. Sadly, Avi Sadeh passed away in the same year this ARR was published. What he left behind was a legacy – including his predecessors (Professor Mary Carskadon), successors and those he inspired, who could be guided by the key findings from his 2016 ARR. These include (a) greater attention to the assessment of sleep in children; (b) sleep research on a wider range of psychiatric disorders; (c) a greater focus on and examination of mechanisms underlying associations; (d) a clearer consideration of developmental questions; and (e) large‐scale well‐designed treatment studies.